Peran Komunikasi Internal Pada Usaha Percetakan Digital Dalam Meningkatkan Kinerja Tim Produksi (Studi Kasus Percetakan Afa Digital Printing Jatiwarna) - Muhari, Muhammad; Ichsan, Muhammad; Nurdiansyah, Chepi (JURNAL ILMIAH NUSANTARA, 2025)
This research is motivated by the importance of internal communication within a company, as demonstrated by AFA Digital Printing Jatiwarna, in improving work effectiveness. The purpose of this study is to identify the patterns of internal communication used to facilitate each objective and goal within the work system. This research aims to analyze the role of internal communication in enhancing the performance of the production team at a digital printing business, with a case study at AFA Digital Printing Jatiwarna.The study employs a qualitative approach with a case study method, based on theories of internal communication, personal communication, and group communication. Data collection techniques include direct observation of work activities, in-depth interviews with the business owner, production team leader, and production team members, as well as documentation of production workflows and related records. The findings reveal that effective internal communication is a key factor in improving coordination, efficiency, and productivity within the production team. The communication pattern implemented at AFA Digital Printing is open, informal yet disciplined, and oriented toward speed and accuracy in information delivery. Relationships among individuals within the organizational structure show strong collaboration, where the business owner plays an active role in providing strategic direction, the team leader acts as a liaison in managing instructions, and the production team performs tasks with a clear understanding of the communicated messages. This research concludes that structured and responsive internal communication can create a productive and synergistic work environment, which directly contributes to improving the performance of the production team.